Relationship Between Clinicians' Inclination Toward Patients at Risk for Suicide (PRS) and Self-reported Countertransference. Issue 1 (2nd January 2023) - Soulié, Tess; Jenkin, Gabrielle; Collings, Sunny; Bell, Elliot
Abstract: Objectives: We investigate the relationship between clinicians' inclination toward treating patients at risk for suicide (PRS), and self-reported countertransference (CT). We consider these observed group differences to explore two competing interpretations for observed CT patterns from a primary study; whether CT patterns are more consistent with defensive attitudes or an adaptative CT montage . Method: We used one-way ANOVA, Tuckey post-hoc, and t -test, to compare clinicians ( n  = 267) grouped by self-ratings of positive, neutral or non-positive inclination toward working with PRS, with regard to their level of endorsement of the Therapist Response Questionnaire (TRQ) with PRS. We hypothesized that positively inclined clinicians would demonstrate greater CT literacy skills than other clinicians, reflected in lower endorsement of negative/hindering CT and higher endorsement of positive/facilitating CT to PRS. Results: Compared to non-positively inclined clinicians, positively inclined clinicians endorsed significantly lower levels of two potentially negative/hindering CT dimensions, factor 1: entrapped/rejecting and, factor 5: protective/overinvolvement, and higher levels of the only positive/facilitating CT dimension, factor 2: fulfilled/engaging. Neutral clinicians reported similar CT patterns to positively inclined clinicians. Conclusions: Hypothesis of greater CT literacy from positively inclined clinicians appears supported. Observed differences in CT endorsement by inclination group tend to support the CT montage interpretation of our original findings more than the defense mechanism interpretation proposed. Similarities in CT patterns between positively inclined and neutral clinicians suggest that positive inclination to PRS, as assessed in this study, may not be countertransferential per se.